CROP WILD RELATIVES IN MAGADAN PROVINCE OF RUSSIA: INVENTORYING AND CONSERVATION - G. V. Talovina; E. V. Aistova (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. Plant genetic resources (PGR) conservation is an indispensable condition for ensuring the country’s economic and environmental security. The most important component of the PGR status assessment is the study of crop wild relatives in a particular region. Within the framework of the work on inventorying crop wild relatives (CWR) in the regions of Russia, an inventory of CWR was for the first time made for Magadan Province, Far East region of Russia, to identify plant taxa that are prioritized for conservation and monitoring of their status in natural phytocenoses. Materials and methods. The material for the present research was taken from the data published on the vegetation of the studied region. Taxonomic analysis of CWR was performed using conventional floristic methods. In order to select priority species for conservation, the guidelines for PGR conservation adapted for Russia were used.Results and conclusions. A list of 232 CWR species belonging to 62 genera of 21 families has been compiled; it encompasses nearly 20% of the entire regional flora. The indigenous part of CWR amounts to ca. 60%, while the adventive part includes 40% of the total CWR number. Analysis of distribution of CWR species over the studied area showed that the greatest diversity of CWR species (81%) is concentrated in the Okhotsky floristic district. As a result of the analysis, 76 species occurring in Magadan Province were identified for prioritized in situ conservation.